An Improved Trust Model Based on Interactive Ant Algorithms and Its Applications in Wireless Sensor Networks. (11th July 2013) - Pan, Yun; Yu, Yafang; Yan, Li
Abstract : Marmol et al.'s ant algorithm based trust model is improved from several aspects: new interactive ant algorithm, new node types, more reasonable meta-assumption on node behaviors, new trust evaluation function, new penalty mechanism, and so on. Simulations on identifying malicious nodes and electing cluster head show that the proposal is effective and can observably reduce the packet drop ratios.